Toshkent xattotlik maktabi va uning vakillari - А.Абдуллаев (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Scientists and calligraphers left an indelible mark on the history of the Tashkent calligraphy school. By the second half of the XIXth century, due to certain economic and political reasons, Tashkent began to become a cultural center. The development of school, education, art and literature prepares the ground for the development of artistic calligraphers engaged in calligraphy in their own way. Tashkent calligraphers organize the sixth calligraphy school of Shahmurad Kotib of Central Asia. The leader of the sixth calligraphy school was Shahmurad Kotib.